2011
DOI: 10.1002/jobm.201000317
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of nine Phytophthora capsici pectin methylesterase genes which are differentially expressed in various plant species

Abstract: Phytophthora capsici causes damage on many plants species, and secretes various pectin methylesterases during all stages of infection. We identified nine Pme genes (Pcpme 1-9) from a genomic library of highly virulent P. capsici strain SD33 and further analyzed the expression pattern of nine genes on three hosts: pepper, tomato, and cucumber using qRT-PCR during all stages of infection. All nine genes were found to be differentially expressed in three host species in the course of P. capsici interaction. The e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…A previous study in Phytophthora infestans , a pathogen of potato and tomato, revealed that PME expression in that species is highest in the first day of infection [ 15 ]. In contrast, analysis of PME expression in Phytophthora capsici revealed that highest levels of expression occur after one week of infection [ 16 ]. Life cycle differences among P .…”
Section: Introductionmentioning
confidence: 99%
“…A previous study in Phytophthora infestans , a pathogen of potato and tomato, revealed that PME expression in that species is highest in the first day of infection [ 15 ]. In contrast, analysis of PME expression in Phytophthora capsici revealed that highest levels of expression occur after one week of infection [ 16 ]. Life cycle differences among P .…”
Section: Introductionmentioning
confidence: 99%
“…1). As well as being ubiquitous in plants, and frequently manifesting in a staggering number of isoforms (more than 66 for Arabidopsis thaliana) (8,10), PMEs are found in phytopathogenic bacteria and fungi (17)(18)(19)(20)(21)(22)(23)(24)(25)(26) and in Archaea (especially Halobacteriaceae (27)), and they have also been observed in the genomes of several phytophagous insects (28 -30) and in human gut microflora (31). Recently, plant pollen PMEs have been identified as a key human allergen (32,33).…”
mentioning
confidence: 99%
“…The extracellular group includes secreted effectors such as well-known protease inhibitors, cysteine proteases, subtilisin-like proteases and aspartic proteases, which act on targets located in the extracellular space (Kamoun 2006;van der Hoorn and Kamoun 2008), as well as the 18 recently described necrosis-inducing Phytophthora proteins (PcNpp) and the nine pectin methylesterases (Pme) identified in P. capsici strain SD33 Li et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…It has been proposed that secreted necrosis-promoting proteins (NPPs) in P. capsici contribute to the transition from biotrophy to necrotrophy; twelve PcNpp genes are expressed in P. capsici during infection, but their functional roles in the virulence of the oomycete remain unclear . Additionally, pectin methylesterase (PcPme) genes are also expressed during infection, and it has been shown that the exposure of plant tissue to PcPme proteins results in collapsing of the tissue and cell death (Lamour et al 2012;Li et al 2011).…”
Section: Introductionmentioning
confidence: 99%